E-commerce and web technologies : 17th International Conference, EC-Web 2016, Porto, Portugal, September 5-8, 2016, Revised selected papers /: 17th International Conference, EC-Web 2016, Porto, Portugal, September 5-8, 2016, Revised selected papers. (2017) - Unknown
No abstract available